Nutrition Guide for Physicians and Related Healthcare Professionals - Temple, Norman J.; Wilson, Ted.; Bray, George A.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Humana Press, 2017)
Nutrition Guide for Physicians is a desktop reference guide on nutrition and its clinical implications for health and disease through the lifecycle. Presented in a new softcover format and user-friendly style, it serves as a valuable resource of practical information on nutrition for physicians in their daily practice. Nutrition Guide for Physicians is divided into three parts that cross the spectrum of nutritional concerns for improving the practice of medicine. Part One provides basic nutritional principles for physicians. Part Two covers nutrition through the lifecycle and optimal nutrition patterns through all stages of development. Part Three covers diet and its role in prevention, cause and treatment of disease. All chapters include figures and tables that provide useful descriptive and visual reviews. "Key points" and succinct "conclusions" are also provided for each topic. Nutrition Guide for Physicians provides a wide perspective of the impact that nutrition has upon medical practice and will be am indispensable resource for primary care physicians and other medical professionals.
Part I: Nutrition Across the Lifespan -- Pregnancy: Preparation for the Next Generation -- Infants: Transition from Breast to Bottle to Solids -- Young Children: Preparing for the Future -- Nutrition in Adolescence -- Nutritional Challenges of Girls and Women -- Healthy Aging: Nutrition Concepts for Older Adults -- Eating Disorders: Disorders of Under and Overnutrition -- Obesity: Understanding and Achieving a Healthy Weight -- Nutrition Therapy Effectiveness for the Treatment of Type 1 and Type 2 Diabetes: Prioritizing Recommendations Based on Evidence -- Lifestyle Interventions to Stem the Tide of Type 2 Diabetes -- Coronary Heart Disease: Nutritional Interventions for Prevention and Therapy -- Diet and Blood Pressure: The High and Low of it -- Role of Nutrition in Understanding Common Gastrointestinal Disorders -- Nutrition in Patients with Diseases of the Liver and Pancreas -- Medical Nutrition Therapy for Kidney Related Disorders -- Inherited Metabolic Disorders and Nutritional Genomics: Choosing the Wrong Parents -- Food Allergy and Intolerance: Diagnosis and Nutritional Management -- Hone Health: Sound Suggestions for Stronger Bones -- Diet, Physical Activity, and Cancer Prevention -- Vegetarian and Vegan Diets: Weighing the Claims -- Dietary Recommendations for Non-Alcoholic Beverages -- What is Best for the Patient: Abstinence or Moderate Alcohol Consumption? -- Dietary Fiber: All Fibers are not Alike -- Dietary Fate: The Good, the Bad, and the Ugly -- Vitamins: The Essentials -- Mineral Nutrients: from Macro-Level to Ultra Trace -- Issues of Food Safety and Quality: Are "Organic" Food Better? -- What is a Healthy Diet? From Nutritional Science to Food Guides -- Dietary Reference Intakes: Cutting through the Confusion -- Food Labels and Sources of Nutrients: Sorting the Wheat from the Chaff -- Achieving Dietary Change: the Role of the Physician -- Dietary Supplements: Navigating a Minefield -- A Plague of False and Misleading Information -- Drug Interactions with Food and Beverages -- Nutritional Status: An Overview of Methods for Assessment -- Nutritional Considerations following Roux-en-Y Gastric Bypass and Sleeve Gastrectomy.
Keywords: Medicine; Nutrition; General practice (Medicine).; Health promotion; Clinical nutrition; Primary care (Medicine).; Medicine & Public Health; Clinical nutrition; Nutrition; Primary Care Medicine; General Practice / Family Medicine; Health Promotion and Disease Prevention